Extraction of oil from rubber seed by using soxhlet extraction - Mohd Zahid, Muhammad Al’Aqib (2018)
The extraction of oil from rubber (Hevea brasillensis) seed by using solvent extraction is conducted in this study with Soxhlet extraction techniques. The Soxhlet technique is an extraction method to produce high percentage of oil yield and practically easy to use. The effect of rubber seed sizes, effect of solvent type and ratio oil to solvent were examined. Three different sizes of rubber seed is compared based on their extracted oil yield, which is 355, 500 and 700 μm. It is found that rubber seed with 355 μm produced the highest percentage of oil yield of 42.13%, compare to percentage of oil yield for 500 and 700 μm rubber seed which were 37.83% and 18.96% respectively. In these studies, type of solvent which are n-hexane and methanol solvent are compared. The results show that, the percentage of oil yield for the methanol is lower than n-hexane solvent. The effect of mass of rubber seed to solvent ratio are compared between 1:4, 1:5, 1:10using 500 μm rubber seed and n-hexane as the solvent. The highest yield is obtained for ratio 1:4 with 31.39% yield.